Research on Raising the Transport Passability Applying the Heat of Engine Flue Gas - Божок, А. М.; Дуганець, В. І.; Майсус, В. В.; Олексійко, С. Л.; Пукас, В. Л. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
Low-quality of roads due to snow and sleet in winter cause the accidents; waste of fuel; forced tire over inflation; vehicle downtime. Therefore; the improvement of operational indicators shows the need for enhancing practicability in terms of snow and sleet. To increase road practicability in terms of ice and sleet the ice destruction device is offered with the help of of flue engine gases warmth; that is realized by installing the flue gas distribution unit in the structure of central; left and right sides inside which the flaps are fixed on the common axis. The main technological and structural parameters of the device are determined by using methods and recommendations given in the paper. The results of the study suggested a new hitch to improve road practicability of transport means with the help of flue gas engine. The proposed device is simple in design; convenient in operation and maintenance. It’s usage will increase the efficiency of the transport operation in bad winter weather.